Options for Multiple Food Allergies — Food Avoidance or Pharmacologic Treatment? - Wong, Gary W.K. (The New England journal of medicine, 2024)
Food allergy is common, affecting up to 8% of children and 10% of adults in the United States. 1,2 Hospital admission data for food-induced anaphylaxis have shown a clear increasing trend in the United States. 3 Food avoidance and use of rescue treatment if accidental exposure occurs are the only advice options we provide. Various forms of immunotherapy for treating food allergy have been investigated in the past decade. However, adverse reactions including anaphylaxis were found to be very common among patients receiving oral immunotherapy for food allergy. 4 Therefore, patients with severe food allergy, especially those who are allergic to multiple foods, . . .